2007
DOI: 10.1080/13816810701538596
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Vitelliform Macular Detachment and Cuticular Drusen: Exclusion of 6 Candidate Genes

Abstract: Screening of 6 candidate genes detected possibly disease-associated mutations in only 3/28 (10.7%) of patients presenting with PVMD/CD, eliminating these genes as causal for this phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…One recent, small study reported similar findings in a white ethnic group; however, most previous studies on patients of white ethnicity reported smaller differences between the prevalence of GA and CNV. These studies reported that CNV could develop in 3.6-56% of patients in white ethnic groups 4,6,10,12,14 . In Korean patients, CNV was observed in only 6 eyes (3.7%) of 5 patients (6.2%); thus, the frequency of CNV in Koreans appeared to be relatively lower than the frequencies reported in white ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent, small study reported similar findings in a white ethnic group; however, most previous studies on patients of white ethnicity reported smaller differences between the prevalence of GA and CNV. These studies reported that CNV could develop in 3.6-56% of patients in white ethnic groups 4,6,10,12,14 . In Korean patients, CNV was observed in only 6 eyes (3.7%) of 5 patients (6.2%); thus, the frequency of CNV in Koreans appeared to be relatively lower than the frequencies reported in white ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Cuticular drusen are more widely scattered on the fundus, with symmetrical distribution patterns in both eyes. In cuticular drusen, the age of onset is younger and genetic associations are stronger than in AMD 6 8 . In addition, smoking, one of the most important environmental factors in AMD, is weakly associated with cuticular drusen 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This CFH variant was not detected in patients manifesting the combination of vitelliform lesion and cuticular drusen. [13][14][15]…”
mentioning
confidence: 99%
“…40,42,43 However, in our cohort the prevalence of cuticular drusen was higher and 32% of the patients with cuticular drusen had a positive family history of AMD compared to 44% of the patients in a study of Grassi et al 40 Previously, our group demonstrated that heterozygous loss-of-function mutations in the CFH gene are found among family members with cuticular drusen. 35,41 In addition, rare highly penetrant variants in the CFI gene have been identified in patients with cuticular drusen.…”
Section: Familial and Sporadic Amd: Phenotypic Differences And Similamentioning
confidence: 84%